2021
DOI: 10.1073/pnas.2102374118
|View full text |Cite
|
Sign up to set email alerts
|

Ssu72 phosphatase directly binds to ZAP-70, thereby providing fine-tuning of TCR signaling and preventing spontaneous inflammation

Abstract: ZAP-70 is required for the initiation of T cell receptor (TCR) signaling, and Ssu72 is a phosphatase that regulates RNA polymerase II activity in the nucleus. However, the mechanism by which ZAP-70 regulates the fine-tuning of TCR signaling remains elusive. Here, we found that Ssu72 contributed to the fine-tuning of TCR signaling by acting as tyrosine phosphatase for ZAP-70. Affinity purification–mass spectrometry and an in vitro assay demonstrated specific interaction between Ssu72 and ZAP-70 in T cells. Upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Depletion of Ssu72 in T cells can increase the production of distinct signature cytokines, IFN-γ and IL-4 under Th1- and Th2-polarizing conditions, respectively ( 11 ). Consistently, Ssu72-deleted CD4 + T cells show increased expression of IFN-γ, IL-4, IL-17, GM-CSF, and transcription factors, including Tbx21 , Gata3 and Rorc in response to TCR stimulation both in vivo and in vitro ( 10 ). These results indicate that Ssu72 might contribute to the differentiation of naive T cells to CD4 + Th cells and negatively regulate the polarization of naïve CD4 + T cells to effector CD4 + T cells.…”
Section: Ssu72 Phosphatase In Differentiation and Maintenance Of Peri...mentioning
confidence: 88%
See 4 more Smart Citations
“…Depletion of Ssu72 in T cells can increase the production of distinct signature cytokines, IFN-γ and IL-4 under Th1- and Th2-polarizing conditions, respectively ( 11 ). Consistently, Ssu72-deleted CD4 + T cells show increased expression of IFN-γ, IL-4, IL-17, GM-CSF, and transcription factors, including Tbx21 , Gata3 and Rorc in response to TCR stimulation both in vivo and in vitro ( 10 ). These results indicate that Ssu72 might contribute to the differentiation of naive T cells to CD4 + Th cells and negatively regulate the polarization of naïve CD4 + T cells to effector CD4 + T cells.…”
Section: Ssu72 Phosphatase In Differentiation and Maintenance Of Peri...mentioning
confidence: 88%
“…Recent studies have suggested that appropriate coordination of phosphorylation status of TCR-related target molecules by Ssu72 phosphatase can facilitate balanced differentiation between CD4 + T cell lineages ( 6 10 11 13 ). In conditional knock-out mice, in which the Ssu72 gene was deleted from T cells, Ssu72 deficiency augmented the differentiation into Th1 and Th2 lineages, whereas Treg population was reduced ( 10 11 ). Depletion of Ssu72 in T cells can increase the production of distinct signature cytokines, IFN-γ and IL-4 under Th1- and Th2-polarizing conditions, respectively ( 11 ).…”
Section: Ssu72 Phosphatase In Differentiation and Maintenance Of Peri...mentioning
confidence: 99%
See 3 more Smart Citations